An Architectural and Structural Review of Diagrid Structural Reinforcement in High Rise Construction - Harvinder; Rajbala (International Journal of Scientific Research in Civil Engineering, 2025)
In the era of rapid urbanization, the demand for efficient high-rise structural systems has become increasingly significant. This study investigates the architectural and structural performance of diagrid systems compared to conventional frame structures using ETABS software. A comprehensive analysis was conducted on 12-storey and 24-storey building models with varying diagrid angles (50.2°, 67.4°, 74.2°, and 82°). The results identified 67.4° as the optimal angle, significantly enhancing lateral stiffness, minimizing displacements, and reducing material consumption. In the 12-storey model, the diagrid system reduced top displacement by 47%, storey drift by 29%, and base shear by 23%, while saving 47% concrete and 8% steel. For the 24-storey model, storey drift was reduced by 35%, with 13.11% less concrete and 57.9% less steel consumption. The findings demonstrate that diagrid systems offer superior structural performance, material efficiency, and architectural flexibility, making them highly suitable for modern high-rise construction.
Keywords: High rise construction; Diagrid; Storey model; Construction